Trans anal drainage tube use for preventing anastomotic leakage af ter laparoscopic low anterior resection in patients with rec tal cancer a randomized clinical trial - Li Shaotang (结直肠肛门外科)
[Importance] Preventing anastomotic leakage (AL) is crucial for colorectal surgery. Some studies have suggested a positive role of transanal drainage tubes (TDTs) in AL prevention after low anterior resection, but this finding is controversial. [Objective] To assess the effect of TDTs in AL prevention after laparoscopic low anterior resection for rectal cancer. [Design, setting, and participants] This multicenter randomized clinical trial with parallel groups (TDT vs non-TDT) was performed from February 26, 2016, to September 30, 2020. Participants included patients from 7 different hospitals in China who were undergoing laparoscopic low anterior resection with the double-stapling technique for mid-low rectal cancer; 576 patients were initially enrolled in this study, and 16 were later excluded. Ultimately, 560 patients were randomly divided between the TDT and non-TDT groups. [Interventions] A silicone tube was inserted through the anus, and the tip of the tube was placed approximately 5 cm above the anastomosis under laparoscopy at the conclusion of surgery. The tube was fixed with a skin suture and connected to a drainage bag. The TDT was scheduled for removal 3 to 7 days after surgery. [Main outcomes and measures] The primary end point was the postoperative AL rate within 30 days. [Results] In total, 576 patients were initially enrolled in this study; 16 of these patients were excluded. Ultimately, 560 patients were randomly divided between the TDT group (n=280; median age, 61.5 years [IQR, 54.0-68.8 years]; 177 men [63.2%]) and the non-TDT group (n=280; median age, 62.0 years [IQR, 52.0-69.0 years]; 169 men [60.4%]). Intention-to-treat analysis showed no significant difference between the TDT and non-TDT groups in AL rates (18 [6.4%] vs 19 [6.8%]; relative risk, 0.947; 95% CI, 0.508-1.766; P=0.87) or AL grades (grade B, 14 [5.0%] and grade C, 4 [1.4%] vs grade B, 11 [3.9%] and grade C, 8 [2.9%]; P=0.43). In the stratified analysis based on diverting stomas, there was no significant difference in the AL rate between the groups, regardless of whether a diverting stoma was present (without stoma, 12 [5.8%] vs 15 [7.9%], P=0.41; and with stoma, 6 [8.3%] vs 4 [4.5%], P=0.50). Anal pain was the most common complaint from patients in the TDT group (130 of 280, 46.4%). Accidental early TDT removal occurred in 20 patients (7.1%), and no bleeding or iatrogenic colonic perforations were detected. [Conclusions and relevance] The results from this randomized clinical trial indicated that TDTs may not confer any benefit for AL prevention in patients who undergo laparoscopic low anterior resection for mid-low rectal cancer without preoperative radiotherapy.